Training and Research in life support and disasters. Recommendations of experts´ workshop. Cienfuegos,2018 - Víctor René Navarro Machado; Arelys Falcón Hernández; Yenisey Quintero Méndez; Dunia María Chávez Amaro; Olga Lidia Sosa Rodríguez; Aymara Marcia Hernández Cardoso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: the National Project ¨Training and Research in life support and disasters¨ has among its objectives to reduce lethality due to emergencies and to contribute to the quality of medical care, but it requires an academic and organizational structure. Objective: to define teaching and research   methodological elements for the project and for its six courses. Methods: qualitative cross research developed in Cienfuegos (July 10/11, 2018) as part of a national workshop called with this purpose with 83 professionals (74, 69% experts) from six provinces. Techniques as brain storming and focal group were used. For the general and specific recommendations about the courses, the group was divided in six sub-groups finally, these were written together to be exposed. Results: the general proposals are related with an updated, uniform, inter-sectorial, face-to-face academic program which is extended to community till post-graduate courses in health institutions and involves computer technologies. Proposals for the integration to the context in the medical practice include the design  and adherence to behaving protocols and the integration to the re-organization of the emergency system. Conclusion: contents of teaching activities and academic and research strategies, so as their integration  to the context of emergency management, may develop the training and training in life support in the project framework. For the impact in health indicators, it is necessary, in addition, inter-sectorial community work and the organizational improvement of the emergency system.